A Role for PPARβ/δ in Tumor Stroma and Tumorigenesis - Rolf Müller; Martin Kömhoff; Jeffrey M. Peters; Sabine Müller-Brüsselbach (PPAR Research)
Peroxisome proliferator-activated receptor-β/δ (PPARβ/δ) is a transcription factor that is activated by endogenous fatty acid ligands and by synthetic agonists. Its role in the regulation of skeletal muscle fatty acid catabolism, glucose homeostasis, and cellular differentiation has been established in multiple studies. On the contrary, a role for PPARβ/δ in tumorigenesis is less clear because there are contradictory reports in the literature. However, the majority of these studies have not examined the role of PPARβ/δ in the tumor stroma. Recent evidence suggests that stromal PPARβ/δ regulates tumor endothelial cell proliferation and promotes differentiation leading to the properly orchestrated events required for tumor blood vessel formation. This review briefly summarizes the significance of these studies that may provide clues to help explain the reported discrepancies in the literature regarding the role of PPARβ/δ in tumorigenesis.